1954
DOI: 10.1152/ajplegacy.1954.178.2.331
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Summating Potential in Cochlear Responses of Guinea Pigs

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1957
1957
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Opposing polarity generation of IHC to OHC has been suggested in the literature since SP's infancy. Many have concluded that IHC generate a positive deflection and OHC a negative one (Goldstein 1954;Johnstone & Johnstone 1966;Helmstaedter et al 2018;Pappa et al 2019), which is consistent with the findings in our study. However, the inverse has also been described (Davis et al 1958;Dallos & Cheatham 1976;Rea & Gibson 2003).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Opposing polarity generation of IHC to OHC has been suggested in the literature since SP's infancy. Many have concluded that IHC generate a positive deflection and OHC a negative one (Goldstein 1954;Johnstone & Johnstone 1966;Helmstaedter et al 2018;Pappa et al 2019), which is consistent with the findings in our study. However, the inverse has also been described (Davis et al 1958;Dallos & Cheatham 1976;Rea & Gibson 2003).…”
Section: Discussionsupporting
confidence: 93%
“…The composition and cellular generators of the SP have long been contended. Some early work described three separate generators (OHC, inner hair cells [IHC], and ANF) of d.c. deflection with different amplitude and polarity qualities ( Goldstein 1954 ). Others have contended solely OHC ( Dallos & Cheatham 1976 ) or primarily IHC generation ( Zheng et al 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…The SP evoked by a tone burst or noise burst gives rise to a DC voltage shift from baseline that continues over the duration of the stimulus. The SP is thought to arise predominantly from the IHC or its afferent terminal ( Goldstein, 1954 , Tasaki et al., 1954 , Davis et al., 1958 , Dallos et al., 1972 , Ding et al., 1993 , Ding et al., 1996 , Ding et al., 2010b , Zheng et al., 1997 , Ding and Jin, 1998 , Durrant et al., 1998 ). Diuretics typically induce a high positive SP no matter if the original polarity was positive or negative; this effect recovered slowly in conjunction with the recovery of the EP and CM ( Syka and Melichar, 1985 , Rybak, 1993 , Ding et al., 1996 , Ding et al., 2004 , Ding et al., 2010b ).…”
Section: Reversible Diuretics-induced Changes In Cochlear Potentialsmentioning
confidence: 99%
“…The behaviour of SP during anoxia is similar to CM in that it is reduced as + EP falls. However, it may change its polarity twice during the fall of +EP (Goldstein, 1954). Neither SP or CM have a latency and they both change phase or polarity when an electrode travels from scala tympani to scala media.…”
Section: Summating Potentialsmentioning
confidence: 99%